Pregnant Women Of Advanced Maternal Age Present Higher Risk Perinatal Maternal Than Adolescent Pregnant Women - Ayala-Peralta, Félix (2017)
Objective: determine if gestation in advanced maternal age is associated with a higher risk of maternal perinatal complicationsthan in adolescent gestation. Materials and methods: observational, correlational, retrospective, cross-sectional study wascarried out with a population of 6475 pregnant women and 7645 pregnant women attended at the National Maternal PerinatalInstitute who have been controlled and culminated in the institution in the period between January From 2012 to December2015.